Developing of Online-Based Mathematical Evaluation Instruments - Hasmita Hasmita; Akbar Nasrum; Herlina Herlina (JME (Journal of Mathematics Education), 2021)
The purpose of this research is to create a mathematical evaluation tool that has been scientifically tested so that it is declared feasible and practical for use in the evaluation process. This research is a research development (Research and Development) and the research model used is the Plomp model which consists of four stages, namely: initial investigation; design stage; realization; tests, evaluations, and revisions. The software used to develop the evaluation tool is Ispring Suite. In terms of data collection, the research instruments used were material validation sheets, media validation sheets, and student assessment response questionnaires. The validation results of the material validator get the final percentage of 84% with the criteria feasible. The validation results from the media validator get a final percentage of 80% with the feasible category. In the assessment of students, the final percentage was 83% with very attractive criteria. It is concluded that the evaluation tool in the form of an online test developed is very suitable for use as an evaluation tool in mathematics learning.